Altered Cortical Synaptic Plasticity in Response to 5-Hz Repetitive Transcranial Magnetic Stimulation as a New Electrophysiological Finding in Amnestic Mild Cognitive Impairment Converting to Alzheimer’s Disease: Results from a 4-year Prospective Cohort Study - Trebbastoni, Alessandro; Pichiorri, Floriana; D’Antonio, Fabrizia; Campanelli, Alessandra; Onesti, Emanuela; Ceccanti, Marco; de Lena, Carlo; Inghilleri, Maurizio (Frontiers in Aging Neuroscience, 2016)
Introduction: To investigate cortical excitability and synaptic plasticity in amnestic mild cognitive impairment (aMCI) using 5Hz repetitive transcranial magnetic stimulation (5Hz-rTMS) and to assess whether specific TMS parameters predict conversion time to Alzheimer’s disease (AD). Material and Methods: Forty aMCI patients (single- and multi-domain) and twenty healthy controls underwent, at baseline, a neuropsychological examination and 5Hz-rTMS delivered in trains of ten stimuli and 120% of resting motor threshold intensity over the dominant motor area. The resting motor threshold and the ratio between amplitude of the first and the tenth motor-evoked potential elicited by the train (X/I-MEP ratio) were calculated as measures of cortical excitability and synaptic plasticity, respectively. Patients were followed-up annually over a period of 48 months. ANOVA for repeated measures was used to compare TMS parameters in patients with those in controls. Spearman’s correlation was performed by considering demographic variables, aMCI subtype, neuropsychological test scores, TMS parameters and conversion time. Results: Thirty-five aMCI subjects completed the study; 60% of these converted to AD. The baseline resting motor threshold and X/I-MEP ratio were significantly lower in patients than in controls (p=0.04 and p=0.01). Spearman’s analysis showed that conversion time correlated with the resting motor threshold (0.40) and X/I-MEP ratio (0.51). Discussion: aMCI patients displayed cortical hyperexcitability and altered synaptic plasticity to 5Hz-rTMS when compared with healthy subjects. The extent of these changes correlated with conversion time. These alterations, which have previously been observed in AD, are thus present in the early stages of disease and may be considered as potential neurophysiological markers of conversion from aMCI to AD.